Photodegradation of Polystyrene Films Containing UV-Visible Sensitizers - Pinto, Leticia F.A.; Goi, Beatriz E.; Schmitt, Carla C.; Neumann, Miguel G. (Journal of Research Updates in Polymer Science, 2013)
The photodegradation of polystyrene films has been investigated in the presence of sensitizers such as benzophenone (BP) and thioxanthone (TX). The phototransformations were studied by infrared and UV-Vis spectroscopy. The results indicate that these photosensitizers accelerate and increase the efficiency of the photodegradation and the photo-oxidation processes in polystyrene and increase the formation of double bonds in the polymer. In all these process, TX showed a larger photosensitization efficiency than BP. Flash photolysis experiments indicate that the triplet reactivity of both sensitizers towards polystyrene are similar, so that the higher efficiency of thioxanthone when compared with benzophenone should be assigned to its larger absorptivity, as well as to the absorptivity of its degradation products in the irradiating region.